How shared is shared decision-making? A care-ethical view on the role of partner and family - van Nistelrooij, Inge (Journal of medical ethics, 2017)
The aim of shared decision-making (SDM) is to provide information to patients in order to enable them to decide autonomously and freely about treatment together with the doctor, without interference, force or coercion by others. Relatives may be considered as hindering or impeding a patient's own decision. Qualitative-empirical research into lived experience of SDM of patients with cancer, however, problematises the patient's autonomy when facing terminal illness and the need to make decisions regarding treatment. Confronted with this difficulty, this contribution tries to think through patients' dependency of others, and make their autonomy more relational, drawing on care-ethical critics of a one-sided view of autonomy and on Ricoeur's view of the fundamentally intersubjective, relational self. We aim to conceptualise relatives not as a third party next to the doctor and the patient, but as co-constituents of the patient's identity and as such present in the decision-making process from the outset. What is more, partners and the family may be of inestimable help in retrieving the patient's identity in line with the past, present and possible future.